2016
DOI: 10.1002/mus.25438
|View full text |Cite
|
Sign up to set email alerts
|

Agrin and low-density lipoprotein-related receptor protein 4 antibodies in amyotrophic lateral sclerosis patients

Abstract: Introduction The prevalence and characteristics of Agrin and LRP4 antibody positive amyotrophic lateral sclerosis (ALS) patients were studied. Methods We tested 82 ALS patients and 59 controls for Agrin and LRP4 antibodies using ELISA. Results We found that 13.8% of ALS patients had Agrin antibodies, and 9.8% had LRP4 antibodies. Women ALS patients are twice as likely as men to have antibodies. Agrin-positive ALS patients are younger than Agrin-negative ALS patients. Discussion Antibodies to Agrin and LR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
45
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(47 citation statements)
references
References 17 publications
2
45
0
Order By: Relevance
“…Previous studies using electromyographic recordings did not identify sex-specific differences in the global time course and pattern of motor axon loss in SOD1 G93A mice (Hegedus et al, 2009) or in ALS patients (McComas et al, 1971;Dengler et al, 1990;Dantes and McComas, 1991;Schmied et al, 1999). Interestingly though, a recent study identified that women with ALS were twice as likely of having antibodies against two NMJ components, agrin and LRP4 (Rivner et al, 2017). Furthermore, Moloney et al (2017) identified sex-specific differences in botulinum toxin-induced axonal sprouting in mice, with female mice notably exhibiting more sprouting from ALS-vulnerable fast-fatigable MUs.…”
Section: Introductionmentioning
confidence: 95%
“…Previous studies using electromyographic recordings did not identify sex-specific differences in the global time course and pattern of motor axon loss in SOD1 G93A mice (Hegedus et al, 2009) or in ALS patients (McComas et al, 1971;Dengler et al, 1990;Dantes and McComas, 1991;Schmied et al, 1999). Interestingly though, a recent study identified that women with ALS were twice as likely of having antibodies against two NMJ components, agrin and LRP4 (Rivner et al, 2017). Furthermore, Moloney et al (2017) identified sex-specific differences in botulinum toxin-induced axonal sprouting in mice, with female mice notably exhibiting more sprouting from ALS-vulnerable fast-fatigable MUs.…”
Section: Introductionmentioning
confidence: 95%
“…6 The possible links between MG and ALS may be represented by immunological dysfunction and shared autoantibodies against neuromuscular junction proteins including low-density lipoprotein receptor-related protein 4. 10 In a previous review of 12 patients with ALS after MG, males were affected twice as often as females, which might reflect a higher incidence of ALS in the male population. 4 Myasthenic symptoms, AChR-ab positivity, and RNST results are not different from those usually found in MG. 4 In addition, clinical features that are specific to ALS after MG might not exist, and the region of ALS onset seems to vary, independently of previous myasthenia symptoms.…”
Section: Discussionmentioning
confidence: 97%
“…LRP4 antibodies were detected in 23.1% of an Italian and Greek population of ALS patients and 14.9% of an Israeli population . In an American population, 9.8% had LRP4 antibodies and 13.8% had agrin antibodies . Interestingly, the incident rate of these antibodies in ALS patients appeared to be higher than that in MG patients.…”
Section: Agrin and Lrp4 Antibodies In Alsmentioning
confidence: 88%
“…67 In an American population, 9.8% had LRP4 antibodies and 13.8% had agrin antibodies. 68 Interestingly, the incident rate of these antibodies in ALS patients appeared to be higher than that in MG patients. However, whether the antibodies are related to ALS development course or clinical symptoms and whether they could serve as a biomarker warrant further studies of larger cohorts with more disease controls.…”
Section: Agrin and Lrp4 Antibodies In Alsmentioning
confidence: 95%
See 1 more Smart Citation